The Role of Interpersonal Communication Intelligence In Supporting Organizational Success in Higher Education - Fadhlan, Fadhlan; Rafles, H.; Raharto, Tito Budi; Bautista, Lloyd C. (International Journal of Multidisciplinary Research of Higher Education, 2023)
The success of an organization is determined by various aspects, including leadership, competence, cooperation and communication. In the aspect of communication, the intelligence organization of a person's interpersonal communication is a very important component. Interpersonal intelligence is one of the intelligences in which a person's ability to establish good social relationships with indicators such as empathy, pro-social attitudes, self-awareness, effective problem-solving abilities, and the ability to communicate effectively. This intelligence is needed by a person in meeting the need for personal competence and social competence. The article aims to explore how important the intelligence of someone's interpersonal communication is in supporting the success of an organization. The methodology used in writing this article is content analysis, one approach to writing scientific work in qualitative research. All data comes from the results of the authors' reading of various theories, expert opinions and the results of previous research related to the issues discussed. All data is then collected, reduced, presented and closed with conclusions. The results of the discussion of this article are expected to be used as additional reference material for the community, academics, subsequent researchers who will discuss this issue in different contexts and issues.